RAS++: representing hybrid reuse assets for MDE as a service - Basso, Fábio Paulo (2017)
Artifacts associated with Model-Driven Engineering (MDE) such as model transformations, Domain Specific Languages (DSL), and modeling or refinement tools have been proposed in the literature as a mean to increase the quality in products derived from activities of Software Engineering. These artifacts are introduced in technical-level settings, including DSLs adopted by model transformation engines, software project workspaces, and other ways to represent tool chains. In technical terms, a successful MDE introduction in target contexts includes the execution of integration phases that establish customized tool chains. This customization has been performed by software engineers in the called “MDE as a Service”, where new opportunities for tool chain are available in asset repositories through coopetition scenarios (collaboration between competing companies). Coopetition benefits market leaders and their competitors and may help promoting MDE adoption. This way, it is necessary a common/hybrid representation for assets and tool chain, which represents a limitation in the state of the art. By including properties from MDE Artifact repositories and tool chain representations, a common representation would simplify the integration of scenarios for coopetition in MDE, allowing automatic transformation of structural features from a scenario to another one. Thus, we proposed RAS++, a new representation language for hybrid assets. Our research results indicate that RAS++ is representative enough to support implementations of MDE as a Service in evaluated coopetition scenarios.